2008
DOI: 10.1007/bf03327508
|View full text |Cite
|
Sign up to set email alerts
|

Is there evidence that religion is a risk factor for eating disorders?

Abstract: This literature search raises the possibility that there is an association between Islamic affiliation and positive screening for eating disorder behaviors. This supports the hypothesis that the effect of culture on eating disorders may be religious as well as secular. Carefully designed studies of the prevalence of eating disorders in multicultural populations with multiple religious affiliations may help further clarify the relationship between religion and eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…While an ideal for heavier body image may protect black females from developing anorexic-type eating disorders [88], it may increase their risk of overweight [89]. Abraham and Birmingham [18] found that Muslim adolescent girls and adult women have a higher prevalence of elevated Eating Attitude Test scores compared to nonMuslim.…”
Section: Sociocultural and Economicmentioning
confidence: 99%
See 1 more Smart Citation
“…While an ideal for heavier body image may protect black females from developing anorexic-type eating disorders [88], it may increase their risk of overweight [89]. Abraham and Birmingham [18] found that Muslim adolescent girls and adult women have a higher prevalence of elevated Eating Attitude Test scores compared to nonMuslim.…”
Section: Sociocultural and Economicmentioning
confidence: 99%
“…This growing concern has led many of them to adopt dietary modifications that potentially throw serious threat on psychosocial development, nutritional status, and development of eating disorder. A number of factors like family environment [7][8][9], peer pressure [10][11][12], media habits [13,14], concern over body image [15][16][17], sociocultural and economic context [7,16,18], gender [6], and age [19] make them feel dissatisfied with their body shape and weight.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are reporting high prevalence of problematic eating attitudes among Muslim populations (e.g., Latzer, Azaiza, & Tzischinsky, 2009;Thomas, Khan, & Abdulrahman, 2010;Mousa, Al-Domi, Mashal, & Jibril, 2010;Abraham & Birmingham, 2008). Interestingly, significant gender differences were not noted in Arab countries (Schulte & Thomas, 2013;Latzer, Azaiza, & Tzischinsky, 2009) but noted in Pakistan (Memon et al, 2012).…”
Section: Disordersmentioning
confidence: 99%
“…31 Usage of English language at home and religion could also be a potential cause of higher tendency for thinking about dieting and body shape, and as an indicator of acculturation. 32,33 …”
Section: Socio-cultural Factormentioning
confidence: 99%